Digitization: An empirical study on Clients’ Perspective (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Digitization is a process of increasing the  reach and capacity of the financial service  providers. It enhances the process of financial  inclusion. The Government of Indian and  other institutes are making tremendous efforts  to increase the reach of financial services, still  among the rural population it is very low. The  innovations in digital modes of transactions  has increased the capacity of the financial  service providers manifolds. Hence, the present  study was conducted to analyze the impact of  digitization in rural parts of Assam. The business  correspondents of four banks, their customers,  and parameters of digital infrastructure in the  location was studied. It was observed that in the  selected location financial and digital literacy  among the borrowers is low. The reasons cited  by the customers for not using digital modes  of transactions are related to their low level  of awareness about the product and lack of  confidence.
Keywords: Digitization; Digital Financial; Inclusion; Digital India; Digital Payments